KEBIJAKAN PEMERINTAH PADA BIDANG PERLINDUNGAN SUMBER DAYA GENETIKA LAUT DI INDONESIA DALAM RANGKA MENJAGA DAN MENGELOLA SUMBER DAYA ALAM LAUT - Atsar, Abdul (Legality : Jurnal Ilmiah Hukum, 2018)
Indonesia is a country that has a wealth of marine genetic resources of interest to researchers and scientists to do research in order to produce findings and new innovations. Thus, the necessary arrangements are clear and unequivocal. The implementation of the system of intellectual property rights requires not only good legislation in the field of intellectual property, but also need to be supported by the Administration, the rule of law as well as the optimal dissemination programs about intellectual property rights. At present, Indonesia has had a device regulation in the field of intellectual property that protects marine genetic resources, namely Act No. 13 of the year 2016 about patents. Since the year 2000, the filing of the application for intellectual property rights can be made at the offices of the Ministry of Justice and human rights areas. This can be seen with the promulgation of Act No. 13 of the year 2016. Through this Act an awful lot of refinement and the addition of the former patent laws i.e. Law No. 14 of the year 2001. As for the formulation of the problem in this research is how Government policy in the field of the protection of genetic resources of the sea in Indonesia in order to maintain and manage the natural resources of the sea. The results showed that decisive action from the Government in preventing violations of patents in the form of damages for Patent holders that have been used by other parties without permission from the patent holder. It also ordered the violators with stops in producing goods that have been patented.